Seismic Performance Assessment of Ordinary Moment Resisting Frame Equipped with Viscous Dampers under Pulse-Like Earthquakes - Amir Yousefpour; Hamid Mazidababdi Farahani; Mohsen Ali Shayanfar (Shock and Vibration, 2022)
In conventional structures, the earthquake-resistant design is based on flexibility after yielding of structural members to provide a loss of earthquake input energy, while, using dampers, the input energy loss can be concentrated in predetermined points to prevent the nonlinear behavior of the main members that are also in the gravity bearing path. However, near-fault earthquakes might cause unexpected failure and severe structural damage, especially those with the pulse-like effect. A pulsed movement in the near field records in this system will, however, result in unusual behavior. Technology advances and the creation of vibration control systems have helped control this type of behavior since the earthquake forces are applied indirectly to the structure. For further investigation of this issue, in this study, some traditional two-dimensional frames were modeled for 3, 8, and 12 floors. Seven near-fault pulsed and seven far-fault nonpulsed accelerometers are applied. The structural behavior in four modes is examined: (1) without damper and soil-structure interaction effect, (2) without damper and considering soil-structure interaction effect, (3) with damper and considering soil-structure interaction, and (4) with damper without considering soil-structure interaction. Each model is analyzed in OpenSees software under incremental dynamic analysis. Then, the fragility curve is plotted based on the results. The results indicate that frame (4) reaches the failure level at a higher spectral acceleration, which means that the performance of the viscous damper in reducing drift between floors is one of the main criteria for predicting damages. It also shows the effect of soil-structure interaction on increasing the drift between floors and reaching failure at lower spectral acceleration in all models. Also, by comparing the fragility curves of the models under near-field and far-field records, it is found that the probability of failure under far-field documents (without pulse) is less than that under near-field documents (with a pulse).